EXISTENCE AND POSITION OF ISLAMIC ECONOMIC LAWS IN INDONESIA - Angkat Poenta Pratama; Hari Sutra Disemadi; Paramita Prananingtyas (Faculty of Law, University of Muhammadiyah Malang, 2019)
The Islamic economy in Indonesia has the potential to continue to grow and has great benefits for the welfare of the economy. The Islamic economic system has also penetrated the real sector with the presence of several types of sharia businesses that include halal food and medicine, Islamic fashion, and even sharia tourism. This study aims to determine the existence and position of Islamic economic law in Indonesia. The research method used in this study is normative juridical. The existence of the Islamic economy is marked by the mushrooming of Islamic-based financial institutions, for example, Islamic Banking, and Islamic Non-Bank Financial Industry (IKNB). The position of Islamic economic law in the Indonesian legal system is no longer just because of historical demands and population because the majority are Muslim but the needs of the wider community. Sharia economic law is felt to be fair so that it can oversee the welfare of the people aspired by the Indonesian people.